2021
DOI: 10.1371/journal.pone.0250714
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among pregnant women with urinary incontinence: A cross-sectional study in a Malaysian primary care clinic

Abstract: Background Pregnant women have an increased risk of urinary incontinence (UI), affecting their quality of life (QoL). This study aims to determine UI and its relationship with QoL among incontinent pregnant women. Methods This was a cross-sectional study in a semi-urban primary care clinic in Selangor, Malaysia, among pregnant women aged 18 years old and above. The validated study instruments consisted of questions on socio-demography, the International Consultation on Incontinence Questionnaire-UI Short For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Therefore, this study added another line of evidence to our needs assessment studies [ 7 , 54 ], validation study [ 19 ], and formative research [ 26 ] in KEPT app development. The data demonstrated that pregnant women (with moderate-to-low income status) in our healthcare clinics are interested in the mHealth app intervention, indicating readiness for the realm of digital health.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study added another line of evidence to our needs assessment studies [ 7 , 54 ], validation study [ 19 ], and formative research [ 26 ] in KEPT app development. The data demonstrated that pregnant women (with moderate-to-low income status) in our healthcare clinics are interested in the mHealth app intervention, indicating readiness for the realm of digital health.…”
Section: Discussionmentioning
confidence: 99%
“…COM-B was used to select the correct intervention (ie, training the pelvic floor muscle) based on previous studies [ 41 , 42 ]. The PSD component of the system’s credibility and trustworthiness, with the expertise involved in the development, may add to the user’s sense of safety and reliability regarding the KEPT app.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed understanding of at-risk pregnant women was established by conducting a cross-sectional study at a primary care clinic [ 41 ]. Within this study, we also determined the prevalence and severity of UI and its impact on participants’ QoL at a primary care clinic (user’s study setting) [ 41 , 42 ]. The findings from this study provided input for the content of their educational videos and short notes on PFMT, which were captured as frequently asked questions (FAQ).…”
Section: Methodsmentioning
confidence: 99%
“…UI is troublesome, particularly during pregnancy, and affects women’s quality of life physically, emotionally, spiritually, and financially [ 4 - 6 ]. Those who experience it may resort to various methods to deal with the problem, including using pads or incontinence diapers and avoiding social situations because of embarrassment.…”
Section: Introductionmentioning
confidence: 99%